Corruption and Environmental Damage: Evidence from Panel Data in ASEAN-6 - Ikhsan, Ikhsan; Amri, Amri (International Journal of Energy Economics and Policy, 2024)
Environmental damage is a topic of great concern among researchers and receives special attention in global circles. One of the major contributors to environmental damage is the emission of greenhouse gases, such as carbon dioxide. In this research, the influence of corruption on carbon emissions in six ASEAN countries is investigated, using indicators of economic growth, renewable energy, and urbanization. The Fixed Effect Model is used as the method of analysis, and the research data used is from 1996 to 2019, based on its availability. The research findings suggest that there is an existence of Environmental Kuznets Curve (EKC) in the form of an inverted U relationship. Renewable energy has a negative effect, while urbanization has a positive effect on carbon emissions. Additionally, control of corruption has been found to have a positive effect on carbon emissions. Based on these findings, it is essential to promote maximum economic growth, use renewable energy, limit urbanization, and increase control of corruption to help mitigate carbon emissions and environmental damage.